Wybrane aspekty opieki pielęgniarskiej w opiece nad pacjentem z Reumatoidalnym zapaleniem stawów = Selected aspects of nursing care of patients with Rheumatoid arthritis - Marzec, Izabela; Budnik, Marta; Balcerak, Dominika; Galikowska, Anna; Ziegler, Aleksandra; Olszewska, Magdalena (Journal of Education, Health and Sport, 2016)
Marzec Izabela, Budnik Marta, Balcerak Dominika, Galikowska Anna, Ziegler Aleksandra, Olszewska Magdalena. Wybrane aspekty opieki pielęgniarskiej w opiece nad pacjentem z Reumatoidalnym zapaleniem stawów = Selected aspects of nursing care of patients with Rheumatoid arthritis. Journal of Education, Health and Sport. 2016;6(9):345-356. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61987 http://ojs.ukw.edu.pl/index.php/johs/article/view/3807 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Wybrane aspekty opieki pielęgniarskiej w opiece nad pacjentem z Reumatoidalnym zapaleniem stawów Selected aspects of nursing care of patients with Rheumatoid arthritis Izabela Marzec1, Marta Budnik1, Dominika Balcerak1, Anna Galikowska1, Aleksandra Ziegler1, Magdalena Olszewska2 1. Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 2. Wydział Matematyki, Fizyki i Techniki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp: Reumatoidalne zapalenie stawów (RZS) jest to choroba autoimmunologiczna wywołująca głównie stany zapalne tkanki łącznej. Jej przebieg związany jest z symetrycznym zajęciem stawów oraz pozastawowych zmian prowadzących do dysfunkcji wielu narządów. Charakteryzuje ją przewlekły ból, związany ze sztywnością poranną. Cel: Ukazanie problemów pacjenta wynikających z reumatoidalnego zapalenia stawów oraz przedstawienie działań mających na celu ich zniwelowanie. Materiały i metody: Dokonano analizy 11 artykułów naukowych jak i literatury współczesnej, obejmujących tematyką zarówno zakres reumatoidalnego zapalenia stawów jak i opieki pielęgniarskiej nad pacjentem z tym schorzeniem. Posługując się słowami kluczowymi: Reumatoidalne zapalenie stawów, RZS, opieka pielęgniarska, problemy pielęgnacyjne. Wyniki: Opieka pielęgniarska nad pacjentem z reumatoidalnym zapaleniem stawów wynika ze specyficznych symptomów tej choroby. Do głównych założeń opieki pielęgniarskiej zaliczyć można: zmniejszenie bólu, zmniejszenie ryzyka wystąpienia infekcji, zniwelowanie ryzyka wystąpienia powikłań choroby. Wnioski: W reumatoidalnym zapaleniu stawów, ze względu na ograniczoną samodzielność bardzo ważna jest opieka pielęgniarska, której głównym celem jest umożliwienie samodzielnego funkcjonowania w środowisku. Wymaga ona współpracy całego zespołu terapeutycznego z pacjentem i jego rodziną. Słowa kluczowe: reumatoidalne zapalenie stawów, opieka pielęgniarska, problemy pielęgnacyjne. Summary: Introduction: Rheumatoid arthritis is a autoimmune disease which cause esecially inflammations of the connective tissue. Her course is related to the symmetric involvement of joints and the extra-articular changes leading to multiorgan dysfunction. She is characterized by chronic pain associated with morning stiffness. Purpose: Showing patient’s problems arising from rheumatoid arthritis and performance actions aimed at eliminating them. Materials and method: An analysis of 11 scientific articles and the contemporary literature covering the topicof both the scope of rheumatoid arthritis and bursing care of patent with this disease. Using the key words: Rheumatoid arthritis, RA, nursing care, nursing problems. Results: Nursing care of patient with rheumatoid arthritis results from the specific symptoms of the disease. The main objectives of nursing care are: pain reduction, reduce the risk of the infection, eliminating the risk of complications of the disease. Conclusion: In rheumatoid arthritis because of limited autonomy the most important is nursing care, which main reason is enable independent functioning in environment. She requires the cooperation of the whole therapeutic team with patient and his family. Key words: rheumatoid arthritis, nursing care, nursing problems.